RI 3303 Comparison Of Output And Intake Characteristics Of Natural-Gas Wells In Texas Panhandle Field ? Introduction - M. A. Schellhardt (The National Institute for Occupational Safety and Health (NIOSH), 1936)
The Bureau of Mines has made periodic back-pressure tests on numerous gas wells in the Texas Panhandle field during the past several years to study the delivery capacities of the wells under different pressure and operating conditions and to determine the relationships between pressures and rates of delivery from gas wells.4/ However, information regarding the intake capacities of gas-well systems is meager, end in projects involving the flow of gas into porous-rock reservoirs it has been necessary to determine intake capacities of gas wells by trial. Accordingly the fundamental intake characteristics of natural-gas yells have been studied to develop a method for determining intake capacities under different wellhead pressures from data descriptive of the "output" or producing characteristic of the wells.